Analysis Of Dat1 (Slc6a3) Rs27072 Gene Polymorphism, Parenting Style, And Internet Addiction Tendency In Adolescents: A Cross-Sectional Study - Pawallangi Irawan, Andi Ummulkhair; Renaldi, Rinvil; Limoa, Erlyn; Idris, Irfan; Wahid, Isra; Teddy Lisal, Sonny; Syamsuddin, Saidah (Journal of Neonatal Surgery, 2025)
Aims. To determine the relationship between DAT1 (SLC6A3) rs27072 gene polymorphism and parenting style in adolescents with a tendency towards internet addiction. Methods. Cross-sectional study of 443 adolescents aged 10-19 years. Determination of adolescents who have a tendency to internet addiction with the Internet Addiction Diagnostic Questionnaire (KDAI) and meet the inclusion criteria of 84 people with a tendency to internet addiction and 311 people who do not have a tendency to internet addiction. Then the determination of parenting style with the Child Parenting Questionnaire (KPAA). DAT1 (SLC6A3) rs27072 gene polymorphism was examined in 84 people with a tendency to internet addiction and 39 people without a tendency to internet addiction using the PCR-RFLP and restriction enzyme methods. Statistical analysis using the fisher exact test and chi square test to test the relationship between variables with a significance value of p <0.05, and binary logistic regression to predict the probability of an event based on predictor variables. Results. DAT1 (SLC6A3) rs27072 gene polymorphism is significantly associated with the tendency of internet addiction in adolescents, most of whom have GG bands, while adolescents who do not have a tendency of internet addiction mostly have TT and TG bands. Parenting style are significantly associated with the tendency of internet addiction in adolescents, most of whom have exposure (permissive) parenting style, while adolescents who are not addicted to the internet mostly have non-exposure (democratic) parenting style. DAT1 (SLC6A3) rs27072 gene polymorphism and parenting style together are significantly associated with the tendency of internet addiction in adolescents. Conclusion: DAT1 (SLC6A3) gene polymorphism rs27072, especially the G allele, and exposure parenting style, especially the permissive type, are associated with the tendency of internet addiction in adolescents.